Clinical profile, etiological factors and outcome of children with status epilepticus admitted in tertiary hospital: a prospective study - Jeergal, Nazeer A.; Lahari, Darla S. S.; Thobbi, A. N. (International Journal of Contemporary Pediatrics, 2024)
Background: Status epilepticus (SE) is a medical emergency, and its neurological outcome is a concern to every pediatrician in developing countries. The incidence of convulsive SE in children is approximately 10–27/100,000 per year, with the highest incidence in children less than one year of age. Approximately 30% of patients presenting with status epilepticus are having their first seizure. The objective of the study is to evaluate the clinical and etiological pattern of SE and its outcome in children admitted to PICU. Methods: This was a prospective study conducted among 50 patients aged 1 month to 12 years presenting with status epilepticus. The study was conducted over a period of one year from April 2022 to April 2023. Results: A majority of the patients were in the age group of 1-5 years (64%) and higher incidence of male children was observed (74%). Generalized tonic clonic seizure (GTCS) was predominant in 76% of the children and seizure duration was 10-20 minutes in 44% of the children. The most common etiologies were Meningoencephalitis (44%) and febrile seizures (20%). Nearly 70% of the children showed complete recovery with no neurological symptoms and 5 (10%) children died. Conclusions: Status epilepticus is a life-threatening emergency and timely management is essential to prevent morbidity and mortality. CNS infection is a major etiology and majority of the children showed good response with AED treatment.